Isolated Terminal Ileitis in Children. Issue 3 (9th December 2022) - Alper, Arik; Bennett, Aaron; Rottmann, Douglas; Morotti, Raffaella; Escalera, Sandra; Padhye Phatak, Uma; Pashankar, Dinesh S.
Abstract : Isolated terminal ileitis in adults is a well described entity that rarely progresses to Crohn disease (CD), and pediatric literature on this topic is very limited. We describe the prevalence, clinical, endoscopic, histologic, and radiological features, along with long-term outcome of isolated terminal ileitis in our institution. We reviewed charts of 956 children who underwent colonoscopy from 2013 to 2017. Thirty-three children had isolated histologically-defined terminal ileitis. Seventeen children were diagnosed with CD and 16 children had idiopathic terminal ileitis. Children with CD had higher prevalence of abnormal C-reactive protein levels, severe inflammation, and radiological evidence of bowel wall thickening compared with children with idiopathic ileitis. Children with idiopathic ileitis did not develop CD over a follow-up period of 83 months. In contrast to adults, CD is common in children with isolated terminal ileitis and those with idiopathic ileitis do well over long-term. Abstract :